(untitled) (Asian Journal of Medical and Biological Research, 2016)
The population increase has not only increased the fresh water demand but also increased the volume of wastewater generated. Treated or recycled wastewater (RWW) appears to be the only water resource that is increasing as other sources are dwindling. Increasing need for water has resulted in the emergence of domestic wastewater application for agriculture and its relative use. The present study was conducted at the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh during 2013 to evaluate the contribution of wastewater to major soil nutrients (N, P, K, S, Ca, Mg, B and Na) and fluctuation in physicochemical properties of soil (soil pH and Ec) from waste carrying canal at 10 selected sites of Bhaluka Upazila. Three (3) soil samples were collected at 0, 30 and 60 m distances from the waste discharging canals. The pH, EC, N, P, K, S, Ca, Mg, B and Na in soil samples decreased gradually with the increase of distance from waste discharging canal. Maximum concentrations of N at 60 and 0m distance varied from 8400 to 9700, P from 1850 to 5000, K from 4600 to 6000, S from 2000 to 4000, Ca from 7500 to 28800, Mg from 7500 to 7800, B from 90 to 2800 and Na from 2300 to 3100 ?g g-1 in test soil.The results showed better nutrient status of the soil along waste discharge canals. The findings give applicable advice to commercial farmers and agricultural researchers for proper management and use of treated industrial wastewater for agricultural purpose. Asian J. Med. Biol. Res. March 2016, 2(1): 131-137